The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2355/isijinternational.52.1310
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mold Flux on Initial Solidification of Hypo-Peritectic Steel in a Continuous Casting Mold

Abstract: Continuous casting of hypo-peritectic steel was conducted with a pilot slab caster. Such experimental data as local heat flux, thickness of solidified shell or mold flux film, and dendrite primary arm spacing were obtained. On the basis of these experimental results, influence of mold flux on initial solidification in the mold was discussed.With mild cooling by crystallization of mold flux, local heat flux and solidification rate decreased in the mold. The changes in them quantitatively correspond to each othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 14 publications
2
73
1
Order By: Relevance
“…104) Values of R int are shown in Table 2 and it can be seen that R int values tend to be (i) scattered and (ii) larger in simulation experiments [98][99][100][101][102][103][104] than in pilot plant tests. 96,97) The latter finding was attributed to the effect of ferro-static pressure pushing on the shell and reducing R int . 96,97) Given the complexity of the heat transfer process and the difficulties in simulating, accurately, the heat transfer across the slag film, it is suggested that results of the pilot plant trials be adopted until proved wrong.…”
Section: Discussion Of Thermal Conductivity Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…104) Values of R int are shown in Table 2 and it can be seen that R int values tend to be (i) scattered and (ii) larger in simulation experiments [98][99][100][101][102][103][104] than in pilot plant tests. 96,97) The latter finding was attributed to the effect of ferro-static pressure pushing on the shell and reducing R int . 96,97) Given the complexity of the heat transfer process and the difficulties in simulating, accurately, the heat transfer across the slag film, it is suggested that results of the pilot plant trials be adopted until proved wrong.…”
Section: Discussion Of Thermal Conductivity Resultsmentioning
confidence: 98%
“…96,97) The latter finding was attributed to the effect of ferro-static pressure pushing on the shell and reducing R int . 96,97) Given the complexity of the heat transfer process and the difficulties in simulating, accurately, the heat transfer across the slag film, it is suggested that results of the pilot plant trials be adopted until proved wrong.…”
Section: Discussion Of Thermal Conductivity Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The values of viscosity and T br 37,38) are, in general, consistent with values derived from empirical rules but there is a tendency for T br values to be slightly higher than the calculated values, presumably to ensure that the slag film provides a satisfactory slag film. Pilot plant trials 72,73) have shown that the interfacial thermal resistance, R int , is lower than the values measured in simulation experiments which has been attributed to the effect of the ferrostatic pressure on the shell in the plant trials. 72,73) Attempts have been made to increase the melting rate and the slag pool depth by reducing the %C in the powder but frequently this is carried out by adding the carbon in the form of carbon black (with low particle size) which tends to negate any advantages with reducing the %C.…”
Section: Mould Slags For High Speed Castingmentioning
confidence: 93%
“…Pilot plant trials 72,73) have shown that the interfacial thermal resistance, R int , is lower than the values measured in simulation experiments which has been attributed to the effect of the ferrostatic pressure on the shell in the plant trials. 72,73) Attempts have been made to increase the melting rate and the slag pool depth by reducing the %C in the powder but frequently this is carried out by adding the carbon in the form of carbon black (with low particle size) which tends to negate any advantages with reducing the %C. The reduction of the %C can also lead to freezing of the steel meniscus (since carbon combustion leads to reduction in the thermal Best to keep slag rim (C/A) = 0.9-2.0 Crystn C/A<1.5 -LA+ CaF2 C/A >1.5 (C3-xNx)A; Cryst tend min at C/A =1.5 [68]; C3S2Fl followed by CB or C9B3Fl [66] Plant trial Large slag rim + poor lubrication [27] High melting phases promote large slag rims [27] Small slag rims (C/A) = 0.9 to 2].…”
Section: Mould Slags For High Speed Castingmentioning
confidence: 93%